2021
DOI: 10.1002/smll.202105599
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Robust Ferroelectricity in 2D Defective Semiconductor α‑Ga2Se3

Abstract: 2D ferroelectrics with robust polar order in the atomic‐scale thickness at room temperature are needed to miniaturize ferroelectric devices and tackle challenges imposed by traditional ferroelectrics. These materials usually have polar point group structure regarding as a prerequisite of ferroelectricity. Yet, to introduce polar structure into otherwise nonpolar 2D materials for producing ferroelectricity remains a challenge. Here, by combining first‐principles calculations and experimental studies, it is repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…This journal is © The Royal Society of Chemistry 2023 nanothread of Ga 2 Se 3 for its dynamical stability as well as the fact that its 2D counterpart has been synthesized. 48 It is noted that the approach of deriving 1D structures from 2D monolayers, as proposed here, could be extended to chemically analogous systems such as V 2 -VI 3 monolayers. [56][57][58] Ferroelectric switching in x 3 of Ga 2 Se 3…”
Section: Structural Stability Of Xmentioning
confidence: 98%
See 1 more Smart Citation
“…This journal is © The Royal Society of Chemistry 2023 nanothread of Ga 2 Se 3 for its dynamical stability as well as the fact that its 2D counterpart has been synthesized. 48 It is noted that the approach of deriving 1D structures from 2D monolayers, as proposed here, could be extended to chemically analogous systems such as V 2 -VI 3 monolayers. [56][57][58] Ferroelectric switching in x 3 of Ga 2 Se 3…”
Section: Structural Stability Of Xmentioning
confidence: 98%
“…The family of a-III 2 VI 3 (III = Al, Ga, In; VI = S, Se, Te) van der Waals (vdW) materials is predicted to support P OP in an atomic thin monolayer. 20 In particular, layered a-In 2 Se 3 nanoflakes and defective Ga 2 Se 3 nanosheets have been successfully synthesized in experiments, 21,48 both possessing 2D ferroelectricity at room temperatures. Fig.…”
Section: Structural Evolution From 2d To 1dmentioning
confidence: 99%
“…(d) The PFM images after writing box-in-box patterns and hysteresis loops of ∼4 nm thick nanoflakes. Reproduced with permission from ref . Copyright 2021 John Wiley and Sons.…”
Section: D Ferroelectricsmentioning
confidence: 99%
“…Based on this, it is possible to induce out-of-plane polarization by introducing vacancies into 2D materials having a relatively loosely packed structure . As shown in Figure c, Xue et al recently reported that the cubic phase α-Ga 2 Se 3 with a Ga vacancy defect could form a polar structure in which the Ga vacancies are displaced from the adjacent asymmetric barriers with a medium energy barrier . With a high transition temperature of 450 K, the switchable polarization can be maintained in the cubic defective α-Ga 2 Se 3 down to ∼4 nm thickness (Figure d) …”
Section: D Ferroelectricsmentioning
confidence: 99%
“…[29] Therefore, an outstanding question arises as to whether and how the (d − 2)-dimensional boundaries can be effectively tuned without magnetism, especially for 2D SOTIs in experimentally feasible candidates.In recent years, ferroelectric and ferroelastic in 2D materials have received extensive attentions. [30,31] Ferroelastic and/ or ferroelectric transitions enable controllable switches for lots of exciting physical properties, which holds great potential for applications in piezoelectric sensors, mechanical switches, and nonvolatile memory devices. [32] A material has ferroelasticity when it refers to the spontaneous structural polarization and strain-induced transition between the identical stable phases, and has ferroelectricity with switchable electrical polarization through the application of the external electric field.…”
mentioning
confidence: 99%